Injury and illness epidemiology in soccer - effects of global geographical differences - a call for standardized and consistent research studies - Cristiano Eirale; Scott Gillogly; Gurcharan Singh; Karim Chamari (Termedia Publishing House, 2017)
Soccer is the most popular sport in the world. While injuries and illnesses can affect the players' health and performance, they can also have a major economic impact on teams. Moreover, several studies have shown the favourable association between higher player availability and team success. Therefore, injury prevention could directly impact clubs' financial balance and teams' performance via increased player availability. To be able to develop effective methods of injury prevention, it is vital to first determine the scope and the degree of the problem: the mechanisms and types of injuries, their frequency and severity, etc. According to the most widely known prevention model, systematic injury surveillance is the first and most fundamental step towards injury prevention. Since epidemiological studies have shown that injuries and illnesses in soccer players differ from region to region, it is important to establish a specific injuries and illness database in order to guide specific preventive actions. Since Asia is the largest continent, with the highest number of soccer players, and in the light of the long-term research on injuries performed in UEFA clubs, the authors of the present article present the AFC surveillance. Some methodological issues related to this prospective design study are discussed. The definition of injury and illness and the methods to track players' exposure are described along with the potential challenges related to such a vast scale study. This article is also a call for action to have consistent and standardized epidemiological studies on soccer injuries and illnesses, with the aim to improve their prevention.